Adverse neuropsychological effects associated with cumulative doses of corticosteroids to treat childhood acute lymphoblastic leukemia: A literature review. (November 2016) - Pépin, A.J.; Cloutier-Bergeron, A.; Malboeuf-Hurtubise, C.; Achille, M.; Krajinovic, M.; Laverdière, C.; Lippé, S.; Marcoux, S.; Sinnett, D.; Sultan, S.
Abstract: Corticosteroids (CS) are an essential component of childhood acute lymphoblastic leukemia treatments (cALL). Although there is evidence that daily doses of CS can have neuropsychological effects, few studies have investigated the role of cumulative doses of CS in short- and long-term neuropsychological effects in cALL. The aims of this review were to identify the measures used for documenting adverse neuropsychological effects (ANEs) of CS treatment and to study the association between cumulative doses of CS and the presence of ANEs. Twenty-two articles met the inclusion criteria. A variety of measures were used to evaluate outcomes in the domains of emotion, behaviour, neurocognition, and fatigue/sleep. The results suggest that we cannot conclude in favour of an association between the cumulative dosage of CS and ANEs. Yet, several factors including the heterogeneity of measures used to evaluate outcomes and reporting biases may limit the scope of the results. We offer several recommendations that could help improve the future published evidence on ANEs in relation to CS treatment in cALL.